Increasing Value Added Tax (VAT) 12% and Impact on The Economy Society: Systematic Literature Study Approach - Etik Ipda; Prasetiyo, Yudhi (Terbuka Journal of Economics and Business, 2024)
The increase in the Value Added Tax (VAT) rate from 11% to 12% is one of the strategic policies of the Indonesian government to increase state revenues to support sustainable development. This policy is regulated in the Law on Harmonization of Tax Regulations (UU HPP) and aims to expand the tax base and create fiscal justice. This study aims to analyze the impact of the increase in VAT rates on the Indonesian economy using a qualitative method based on a systematic literature review. Data were analyzed from various scientific articles, online news, and related policy reports to provide a comprehensive picture of the implications of this policy. The results of the study show that the increase in VAT rates has a direct contribution to increasing state revenues, which is expected to support the development of infrastructure, education, and health. However, this policy has also raised concerns about the additional burden on people's purchasing power, especially low-income groups, although basic necessities are not included in the scope of VAT. In addition, the analysis shows that this rate increase contributed additional inflation of around 0.2% in the first year of its implementation, which is temporary because it is limited to the initial adjustment phase. Inflation in Indonesia tends to be more influenced by global commodity prices than changes in VAT rates, so its impact on economic growth is projected to be minimal. The long-term success of this policy depends heavily on effective management of state revenues and government transparency in communicating the benefits of the policy to the public. Thus, this VAT rate increase can be an effective tool to support sustainable development if supported by adequate supporting policies.